Comparison of seedling growth among three co-occurring varieties of Araucaria angustifolia (Bertol.) Kuntze under greenhouse conditions - André Luiz Coutinho; Lúcia Rebello Dillenburg (Acta Botânica Brasílica, 2010)
Araucaria angustifolia (Bertol.) Kuntze is a tall, long-lived tree species, which grows as an emergent tree in the araucaria forests of southern Brazil. Four varieties have been described for this species, and three of them were selected for this study: "angustifolia" (the type variety), "caiova" and "indehiscens". These are co-occurring varieties that differ in external seed color and timing of seed maturation. The purpose of this study was to compare the initial growth of plants originated from seeds of these three varieties, in order to test the hypothesis that these varieties also differ in the initial growth of their seedlings. Seeds were collected from a single forest location, and 60 plants per variety were grown in pots for a period of 244 days. The "angustifolia" variety accumulated significantly more mass (both in shoot and root) than the other two, but the three varieties did not differ in mass allocation between shoot and root and between lateral roots and the main root. The greater growth of the type variety may help explain its greater natural abundance, since attaining a larger size will have positive effects on seedling recruitment and survival. Araucaria angustifolia (Bertol.) Kuntze é uma espécie de porte alto e vida longa, que cresce como árvore emergente em florestas de araucária no sul do Brasil. Quatro variedades foram descritas para esta espécie, e três delas foram selecionadas para este estudo: "angustifolia" (variedade típica), "caiova" e "indehiscens". Estas variedades co-ocorrentes diferem umas das outras na coloração externa de suas sementes e em relação ao tempo de maturação das mesmas. O objetivo deste estudo foi comparar o crescimento inicial de plantas oriundas de sementes destas três variedades, a fim de testar a hipótese de que estas variedades também diferem no crescimento inicial das plântulas. As sementes foram coletadas em um mesmo local da floresta, e 60 plantas de cada variedade foram cultivadas em vasos por um período de 244 dias. A variedade "angustifolia" acumulou significativamente mais massa (tanto na parte aérea quanto na raiz) do que as outras duas, mas as três variedades não diferiram na partição de massa entre parte aérea e raiz e entre raízes laterais e a raiz principal. O maior crescimento da variedade típica pode ajudar a explicar a sua maior abundância natural, uma vez que um maior tamanho inicial teria efeitos positivos sobre o recrutamento e sobrevivência da mesma.